Effectiveness of Implementing PCC Load Balancing, Failover, and Time Scheduler Methods for Internet Quality at AKN Aceh Barat - Rial Fauza; Ary Firnanda (Information Technology and Science (ITScience), 2026)
The internet network configuration at the Akademi Komunitas Negeri Aceh Barat uses MikroTik CCR2116-12G-4S+ router devices with two Internet Service Provider (ISP) connections, implementing the load balancing method Per Connection Classifier (PCC), failover, and time scheduler. MikroTik CCR2116-12G-4S+ is a high-performance Cloud Core Router ideal for multi-ISP load balancing like PCC and failover setups in this research. Its ARM-based architecture eliminates CPU bottlenecks in 10G environments. The PCC method is used to distribute network traffic based on connections consistently to maintain internet access stability. The failover mechanism is implemented through routing settings and gateway checks to ensure service continuity during ISP disruptions. Meanwhile, the time scheduler is used to manage network policies based on operational hours. The study results show that the combination of these methods is highly effective in improving connection stability, bandwidth utilization, and reliability of the multi-ISP network, making it suitable for application in network environments with high internet access demands, such as higher education institutions.